1975
DOI: 10.1007/bf01071195
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of gastric emptying time?A comparative study between nonisotopic aspiration method and new radioisotopic technique

Abstract: A comparative study between modified conventional saline load test and the more recently introduced radioisotopic method was run in 8 normal volunteers. Each subject underwent at least three studies by each of the two methods: (1) aspiration method of Goldstein and Boyle incorporating our modification, and (2) an isotopic method employing a gamma camera with a computer. A liquid meal of isotonic saline was used with or without (997) MTc-DTPA. The results indicated that the gastric emptying T 1/2 (8.8 +/- 3.5 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

1977
1977
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…This is a significant factor for a multicompartment dissolution apparatus in the prediction of in vivo dissolution. In this study, the gastric half‐emptying time for the GIS was observed to be between 5 and 10 min, and although it is in general agreement with previous reports of the gastric emptying of liquids, it is shorter than other reported value . This requires direct confirmation by measuring luminal fluid concentrations in the future.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…This is a significant factor for a multicompartment dissolution apparatus in the prediction of in vivo dissolution. In this study, the gastric half‐emptying time for the GIS was observed to be between 5 and 10 min, and although it is in general agreement with previous reports of the gastric emptying of liquids, it is shorter than other reported value . This requires direct confirmation by measuring luminal fluid concentrations in the future.…”
Section: Resultssupporting
confidence: 90%
“…Therefore, it is necessary to develop a dissolution apparatus, the GIS, to simulate gastric emptying to predict better in vivo dissolution. In the human fasted state, it has been reported that liquids gastric half‐emptying time was 4.2, 12, and 15.8 min . In this set of dissolution studies, five different gastric emptying half‐times (5, 10, 15, 20, and 30 min) were tested with the GIS, and pharmacokinetics parameters were obtained by GastroPlus™ based on the dissolution results with the GIS.…”
Section: Discussionmentioning
confidence: 99%
“…Selection of the 30-minute time point for diagnosing rapid gastric emptying was based on the original description of the use of the 200-kcal CMM as well as clinical experience. 11 Normal range for the gastric emptying meal for gastric emptying is defined as 50% emptying of the meal at 30 to 60 minutes. After classifying the 100 patients on the basis of their gastric emptying rate as shown in Table 2, the patients' symptoms were tallied based on the description of the patients' symptoms in the clinical referral and reported for patients in the rapid, normal, and delayed gastric emptying groups.…”
Section: Methodsmentioning
confidence: 99%
“…[2][3][4][5][6] Many different types of meals have been described for use in clinical nuclear medicine studies, including a hamburger meal, 7 a standardized egg white and toast meal, 8 a pancake meal, 9 a mashed potato meal, 10 and a corn flakes and milk meal. 11 The composition of the gastric emptying meal may be related to the frequency with which rapid gastric emptying is diagnosed. Rapid gastric emptying has been more commonly reported when all of the components of a solid meal were labeled with a radiotracer 1 or in meals composed of liquids or semisolids such as mashed potatoes in which the radiotracer is homogeneously dispersed throughout the whole meal.…”
mentioning
confidence: 99%
See 1 more Smart Citation